Kinetic modeling and experimental validation on the effect of KCl and SO2 concentration on corrosion of pure Fe under simulated municipal solid waste combustion. (October 2018) - Ma, Wenchao; Wenga, Terrence; Chen, Guanyi
Abstract: Thermal treatment of municipal solid waste (MSW) in waste-to-energy plants (WtE) has gained worldwide acceptance as an environmentally preferred method for sustainable disposal of waste and energy recovery. However, superheater corrosion induced by large amounts of alkali chloride (KCl) and SO2 released from MSW during combustion remains a major challenge. In this study, a novel kinetic model was developed to study the corrosion behavior of pure Fe-metal and the reaction pathways using chemkin-PRO and Gaussian 09. The model relies on detailed high-temperature interactions between gaseous potassium, O/H radicals, chlorine/sulfur species, and the Fe-metal. The rate coefficients for the surface reactions were estimated based on density functional theory computations using several Fe clusters that represented the Fe metal surface. The model was validated by the experimental results obtained from well-controlled simulated corrosion tests conducted in an electrically heated furnace at 500°C with each test lasted for 50hours. The exposure conditions consisted of 0-600mg KCl which was preheated and its gas was injected into the furnace, 0-1700ppm SO2, 20vol.% H2 O, 8vol.% O2, and N2 as the carrier gas. Comparison of the kinetic model and the experimental data showed there was a good agreement. The results revealed that increasing KCl concentration accelerated the corrosion rate of Fe with a parabolic rate law. The concentration of SO2 > 500ppm enhanced the rate of corrosion of Fe, concentrations between 250-500ppm reduced the corrosion rate, and the concentration < 250ppm had less effects. The reaction series that replenished the Cl radicals and KSO3 Cl promoted the high corrosion rates while reaction path that forms sulfate suppresses it. The effect of supercritical conditions on SO2 and KCl induced corrosion rate were presented and discussed.